2011
DOI: 10.1142/s0218126611007797
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Reversible Zs Gate and Its Application for Optimization of Quantum Adder Circuits

Abstract: The key of optimizing quantum reversible logic lies in automatically constructing quantum reversible logic circuits with the minimal quantum cost. This paper constructs a 4 × 4 reversible gate called ZS gate to build quantum full adder. At the same time, a novel reversible No-Wait-Carry adder (or carry skip adder) by using ZSCGPD based on ZS gate with the least cost is also designed. The adder circuit using the proposed ZSCGPD is much better and optimized than other researchers' counterparts both in terms of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…bits Proposed RCA Square Root CSLA Adder [25] Adder [21] Adder [23] Adder [22] Adder 1 [28] Adder 2 [28] Adder [ square root method, as it results in minimum possible delay and a reasonable quantum cost for the addition operation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…bits Proposed RCA Square Root CSLA Adder [25] Adder [21] Adder [23] Adder [22] Adder 1 [28] Adder 2 [28] Adder [ square root method, as it results in minimum possible delay and a reasonable quantum cost for the addition operation.…”
Section: Resultsmentioning
confidence: 99%
“…In 2011, Haghparast et al represented an n-bits adder structure using the ripple carry method utilizing HNG gates, which results in a total quantum cost and delay of 6n [21]. Zhou et al proposed a reversible adder structure based on the carry look-ahead method [22] to optimize the reversible adder circuit in propagation delay, but their design could not bring about superior results in terms of delay and quantum cost compared to reversible ripple carry circuits. He indicated that although some architectures like the carry look-ahead adders in conventional digital designing methodology provide less propagation delay than the ripple carry method, reversible and quantum designs might contradict these standard rules due to their different optimization objective and designing principles of conventional logic designs.…”
Section: Fundamentals and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…LTL cannot assert the existence of paths. We express the complement property of formula (9) in formula (10).…”
Section: -9mentioning
confidence: 99%
“…8,12 Many algorithms were proposed in literature to perform reversible logic synthesis and optimize their performance metrics. 13,14 Two new reversible logic gates known as TSG gate 15 and ZS gate 16 were proposed to design quantum circuits. In addition, di®erent structures of reversible adders 17,18 and reversible multipliers 19,20 were proposed to design reversible arithmetic and logic unit (ALU).…”
Section: Introductionmentioning
confidence: 99%